Las redes sociales para fomentar la interculturalidad en la educación superior (Investigaciones) - Diaz Quichimbo, Danilo Marcelo (2022)
This article analyzes the relationship between social networks and intercultural practices in higher education. A qualitative approach was applied through an action-research methodology and a descriptive technique. As a result, it was obtained that social networks promote interculturality due to their multiple advantages: communication, interaction, ease of use, and participation in the educational community. It was possible to encourage the practice of intercultural principles and the appreciation of the use of social networks in an innovative way and the generation of spaces in which teachers foster the presence of cultural values in the educational field among students.